Pilgrim Loyalty Development Through Satisfaction and Sharia-Compliant Service Quality (Case Study: Umrah Travel Agencies in AMPHURI SULAMPUA) - Sastri Ayu Wiranitania; Murtiadi Awaluddin; Nasrullah Bin Sapa (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2025)
This study aims to examine the satisfaction and loyalty of pilgrims through Sharia-compliant service quality in Umrah travel companies under AMPHURI SULAMPUA. The research is grounded in the regulations set forth by Ministerial Regulation No. 8 of 2018 concerning the Organization of Hajj and Umrah. These serve as essential foundations to ensure that Hajj and Umrah travel services comply with existing Sharia standards. The type of research used is quantitative with a causal associative research design. This study collected primary data from 150 respondents using a purposive sampling technique. The data were analysed using the Structural Equation Modelling (SEM) method with the Partial Least Squares (PLS) version 4.0 approach. The results show that Sharia-compliant service quality—measured by reliability, responsiveness, assurance, empathy, tangibles, and Sharia compliance—has a positive and significant effect on pilgrims’ satisfaction. Similarly, Sharia-compliant service quality has a positive and significant effect on pilgrims’ loyalty. Furthermore, pilgrim satisfaction has a positive and significant effect on loyalty. The mediating effect of satisfaction strengthens the relationship between Sharia-compliant service quality (based on reliability, responsiveness, assurance, empathy, tangibles, and Sharia compliance) and pilgrim loyalty, and this effect is also positive and significant. The implication of this study is that Umrah pilgrims served by travel companies under AMPHURI SULAMPUA place greater emphasis on Sharia-compliant service quality in order to attain satisfaction and ultimately build loyalty toward the offered products or service packages.